Integrating anaerobic digestate effluent into microalgal systems for renewable biomass and wastewater treatment: Effects of dilution, C/N ratio, and growth modelling - Dhomas Indiwara Prana Jhouhanggir; Ambar Pertiwiningrum; Nanung Agus Fitriyanto; Eko Agus Suyono (Results in Engineering)
This study investigated the potential of anaerobic digestate effluent (ADE) as a nutrient source for cultivating Euglena sp. and Chlorella sp. ADE was applied at varying dilution levels to create distinct carbon-to-nitrogen (C/N) ratios and assess their effects on microalgal growth and nutrient removal. The research included an acclimatisation phase using a mixture of 75% Walne medium and 25% ADE to facilitate adaptation, followed by cultivation with ADE dilutions without added nutrients. This mixture supported optimal initial growth, indicating ADE’s viability as a nutrient source. Post-acclimatisation, three ADE dilution treatments established distinct C/N ratios: P1 (8.24 ± 1.32), P2 (6.47 ± 1.15), and P3 (4.39 ± 0.41), with P0 (Walne medium) as control. One-way ANOVA and Duncan’s Multiple Range Test (DMRT) revealed significant differences among treatments. Both species adapted to ADE, showing optimal growth at a C/N ratio of 6.47 ± 1.15 (P2). Under controlled conditions (28 ± 1 °C, pH 7.5 ± 0.2, 20 days cultivation), P2 achieved the highest cell density and pollutant removal. Euglena sp. removed 81.44 ± 1.40% Chemical Oxygen Demand (COD), 84.25 ± 0.79% Biological Oxygen Demand (BOD₅), 61.16 ± 2.60% Total Suspended Solid (TSS), and 88.86 ± 2.25% Ammonium (NH₄⁺-N), while Chlorella sp. achieved 89.02 ± 0.84% COD, 87.33 ± 1.34% BOD₅, 64.73 ± 3.33% TSS, and 89.45 ± 1.29% NH4⁺-N. P2’s superior performance was attributed to its balanced nutrient profile and reduced inhibitory effects associated with higher organic and ammonium levels in less-diluted ADE. These findings support ADE as a sustainable medium for microalgal cultivation, enabling biomass production and effective wastewater treatment. Optimising dilution enhances growth and environmental outcomes, underlining microalgae’s role in the circular bioeconomy and sustainable agriculture.